Speech@Home:An Exploratory Study - Brush, A.J.; Inkpen, Kori; Johns, Paul; Meyers, Brian (CHI 2011, 2011)
To understand how people might use a speech dialog system in the public areas of their homes, we conducted an exploratory field study in six households. For two weeks each household used a system that logged motion and usage data, recorded speech diary entries and used Experience Sampling Methodology (ESM) to prompt participants for additional examples of speech commands. The results demonstrated our participants’ interest in speech interaction at home, in particular for web browsing, calendaring and email tasks, although there are still many technical challenges that need to be overcome. More generally, our study suggests the value of using speech to enable a wide range of interactions.